Membudayakan Kepemimpinan Transformatif di Lembaga Pendidikan Islam - Moh. Syamsul Falah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2016)
Culture is very important to build leadership spirit in the organization, particularly in transformative leadership. Because the transformative leader is unique and interesting to observe, given the transformative leader always bring an adaptive culture present, so that members of the organization feel terayomi and motivated by the existing leadership patterns. Transformative leadership also gives uswah and instill positive values ​​in subordinates, if this transformative leadership applied in Islamic educational institutions, then it would become more attractive given the current transformative studies began to appear prophetic. This leadership style is very pleasant subordinates because they feel involved and directed into those great confidence and responsibility together with the members of his organization. Moreover, this in Islamic educational institutions still professional leadership crisis with their pattern of prophetic transformative leadership, the Islamic educational institutions will experience significant progress